Pendidikan Kesehatan Bahaya Merokok Sebagai Pencegahan Perilaku Adiksi Anak Usia Sekolah di Madrasah Ibtidaiyah Hayatul Islamiah: Pendidikan Kesehatan Bahaya Merokok Sebagai Pencegahan Perilaku Adiksi Anak Usia Sekolah di Madrasah Ibtidaiyah Hayatul Islamiyah - Suratmini, Dwi; Firmansyah, Robby; Salsabila, Audy (Jurnal Pengabdian Masyarakat Kesehatan Terkini, 2024)
Smoking is one of the behaviors that risks causing various health problems, both physical and mental health. The prevalence of smokers increases every year, including in the school-age child population. School-age children are in a vulnerable critical period to external environmental influences. Health education is carried out so that children know the dangers of smoking to prevent it from developing into addictive behavior. This activity was carried out on 31 students in grade 6 of the Hayatul Islamiah Elementary School through lectures, discussions, and demonstrations. The results showed that health education for school-age children can increase students' knowledge about the dangers of smoking. This action can be used as a preventive measure to prevent addictive behavior in the future. Health education about the risks of smoking should be carried out continuously by involving the participation of the child's closest environment.